Search for the decay KS → π0γγ - Lai, A; Marras, D; Batley, R; Bevan, A; Dosanjh, R; Gershon, T; Kalmus, G; Munday, D; Olaiya, E; Parker, M; White, T; Wotton, SA; et al. (2003)
A search for the decay KS → π0γγ has been made using the NA48 detector at the CERN SPS. Using data collected in 1999 during a 40-hour run with a high-intensity KS beam, an upper limit for the branching ratio BR(KS → π0γγ, z ≥ 0.2) < 3.3 x 10-7 has been obtained at 90% confidence level, where z = m2γγ/mKO2. © 2003 Published by Elsevier Science B.V.